Physical and hydraulic properties of aridisols as affected by nutrient and crop-residue management in a cotton-wheat system - doi: 10.4025/actasciagron.v35i1.14683 - Muhammad Mahmood-ul-Hassan; Eajaz rafique; Abdul Rashid (Acta Scientiarum. Agronomy, 2012)
A 5-year cotton–wheat rotation field experiment was conducted on two alkaline-calcareous soils to investigate the impact of integrated nutrient-management and crop-residue incorporation on soil physical and hydrological properties. The nutrient treatments were: T1–farmers' fertilizer use; T2–balanced nutrient management (recommended N, P, Zn. and B from mineral sources); T3–integrated nutrient management, same as T2, except that 75% N was applied from fertilizer and 25% as FYM; and T4 same as T2, except that every alternate year, wheat was substituted by Berseem green manure. All treatments were compared with and without crop residue incorporation. Soil organic matter (SOM) content in both the soils was significantly increased with T2, T3 and T4 as compared with T1, and was increased further where the nutrient-management treatments were applied in combination with crop-residue recycling. Higher increase in SOM content was observed in soil having relatively lower initial SOM (0.61%) than soil having initial 0.80% SOM content. Increased SOM content, in return, decreased soil bulk density, improved macro- and meso-porosity, and enhanced percent recovery of stable aggregates correspondingly. Infiltration rates were 20, 49 and 26% higher with T2, T3 and T4, respectively, over T1 and 64% higher with crop-residue incorporation over crop-residue removal. Positive impacts on soil physical properties were also observed in the sub-soil layers.